The Overlooked Role of the Stratosphere Under a Solar Constant Reduction. Issue 12 (24th June 2022) - Bednarz, Ewa M.; Visioni, Daniele; Banerjee, Antara; Braesicke, Peter; Kravitz, Ben; MacMartin, Douglas G.
Abstract: Modeling experiments reducing surface temperatures via an idealized reduction of the solar constant have often been used as analogs for Stratospheric Aerosol Injection (SAI), thereby implicitly assuming that solar dimming captures the essential physical mechanism through which SAI influences surface climate. While the omission of some important processes that otherwise operate under SAI was identified before, here we demonstrate that the imposed reduction in the incoming solar radiation also induces a different stratospheric dynamical response, manifested through a weakening of the polar vortex, that propagates from the upper stratosphere down to the troposphere. The coupled stratospheric‐tropospheric response exerts a previously overlooked first‐order influence on southern hemispheric surface climate in the solar dimming experiments, including on the position of the tropospheric jet and Hadley Circulation and thus, ultimately, precipitation patterns. This perturbation, opposite to that expected under SAI, highlights the need for caution when attributing responses in idealized experiments. Plain Language Summary: Adverse impacts of climate change have pushed research on temperature reduction strategies like geoengineering into the spotlight. Possible impacts of geoengineering have long been assessed using "solar dimming" climate model experiments, which reduce surface temperatures via an idealized reduction of the incoming solar radiation as an analogue for injecting sulfate aerosols into the lower stratosphere (Stratospheric Aerosol Injection, SAI). We demonstrate that solar dimming induces previously overlooked circulation changes in the stratosphere that propagate down to the troposphere and exert a first‐order influence on the Southern Hemisphere surface climate. This allows for an erroneous attribution of the simulated surface responses to the impacts of SAI geoengineering. The results also emphasize the importance of the stratosphere as an active contributor to the Southern Hemisphere near‐surface climate change, and have implications for paleoclimate studies. Key Points: Solar dimming induces previously overlooked stratospheric dynamical response The coupled stratospheric‐tropospheric response exerts a first‐order influence on the Southern Hemisphere (SH) surface climate in the solar dimming experiments The results emphasize the importance of the stratosphere, as well as the troposphere, as an active contributor to the SH climate change